Breast Cancer Updates - Sözen, Selim; Emir, Seyfi (IntechOpen, 2023)
Breast cancer is the neoplasia with the highest incidence in the female population worldwide. Cancer originates from breast tissue, most commonly from the inner lining of milk ducts or the lobules. Histologic type, tumor grade and size, expression of ER, PR, and HER2 receptors, and lymph node and metastasis status are considered important prognostic factors. This book provides a comprehensive overview of breast cancer with chapters on breast cancer markers, breast cancer in different populations, imaging, minimally invasive techniques, breast reconstructive surgery, and much more.